Pengaruh Keseimbangan Kehidupan-Kerja, Keterlibatan Karyawan dan Kepuasan Kerja Terhadap Kinerja Karyawan - Dinda Permatasari; Dewi Andriani; Vera Firdaus (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to determine the effect of work-life balance, employee involvement and job satisfaction in improving the performance of PERUMDA Delta Tirta Sidoarjo employees both partially and simultaneously. The research method used is a quantitative method using a 1-5 Likert scale analysis tool which is then tested using SPSS 24 software. The data collection technique in this study used a questionnaire distributed via a google form link. The population in this study were all employees who worked at the Head Office of PERUMDA Delta Tirta Sidoarjo, totaling 363 people. The sample size in this study was 190 determined using the slovin formula. The sampling method used is non probability sampling using proportional random sampling. The results of this study indicate that work-life balance, employee involvement and job satisfaction partially and simultaneously have a positive and significant effect in improving the performance of PERUMDA Delta Tirta Sidoarjo employees. From the results of the coefficient of determination, it is known that the magnitude of the contribution of work-life balance variables, employee involvement and job satisfaction affects employee performance variables by 46.7% and the remaining 53.3% is influenced by other variables not used in this study.